Analisis Pendapatan Usaha Budidaya Selada Caipira (Lettuce Caipira) Hidroponik Di Setya Agrofarm Kecamatan Boja, Kabupaten Kendal - Muhammad Chabib Al Chudri; Rossi Prabowo; Endah Subekti; Istanto Istanto (Universitas Wahid Hasyim, 2025)
Hydroponic vegetables are a type of vegetable that is cultivated using water planting media that has been added with organic and chemical nutrients. Hydroponic vegetables are widely cultivated commercially in urban areas due to the lack of agricultural land, but over time hydroponic vegetables are also in great demand by many people in the region. Boja District, Kendal Regency, Central Java is one of the areas where the level of hydroponic vegetable consumption continues to increase from year to year. Setya Agrofarm is one of the business ventures located in Boja District and is engaged in the agricultural sub-sector, especially hydroponic vegetables. The purpose of this study is to determine the income, revenue, and R/C generated from hydroponic vegetable cultivation business within 1 planting period. The method carried out in the study is a research method by determining the research location deliberately (purposive). The results of the study show that the average revenue is Rp. 2,166,667, the average income is Rp. 1,345,500, and the average R/C value is 2.6 from the average land area of 120M2. Based on the criteria of the decision that has been set, where R/C > 1 shows that the business is feasible to be implemented, all plantations in this analysis meet the requirements for business feasibility